Feasibility and safety of specimen extraction via an enlarged (U-Plus) skin bridge loop ileostomy: a single-center retrospective comparative study - Xiang, Shang; Huang, Shujuan; Ye, Hui; Lu, Wei; Zeng, Xiangsheng (Frontiers in Oncology, 2023)
Objective To investigate the feasibility and safety of specimen extraction via an enlarged (U-Plus) skin bridge loop ileostomy. Methods A retrospective analysis of 95 patients with rectal cancer who underwent laparoscopic low anterior rectal resection and skin bridge loop ileostomy between August 2018 and August 2022, including 44 patients with specimen extraction via an enlarged (U-Plus) skin bridge loop ileostomy (experimental group) and 51 patients with specimen extraction via an abdominal incision (control group). Following the application of propensity score matching (PSM), 34 pairs of data were successfully matched. Subsequently, a comparative analysis was conducted on the clinical data of the two groups. Results The experimental group exhibited significantly better outcomes than the control group in various aspects. Specifically, the experimental group had lower values for average operative time (P < 0.001), estimated blood loss (P < 0.001), median length of visible incision after surgery (P < 0.001), median VAS pain score on the first day after surgery (P = 0.015), and average postoperative hospitalization (P = 0.001). There was no statistical significance observed in the incidence of stoma-related complications in both groups (P > 0.05). Within each group, the stoma-QOL scores before stoma closure surgery were significantly higher than those at one month and two months after the surgery, with statistical significance (P < 0.05). Conclusion Specimen extraction via a U-Plus skin bridge loop ileostomy is a safe and feasible method that shortens operation time and postoperative visual incision length, decreases estimated blood loss, and reduces patient postoperative pain compared with specimen extraction via an abdominal incision.